Drivers of trade finance gaps - Alisa DiCaprio; Ying Yao (Asian Development Bank Institute (ADBI), 2017)
Banks are a critical facilitator of trade. Without bank-intermediated trade finance, global exports and imports would come to a halt. This has been apparent during the episodes of credit rationing that accompany financial shocks. But we have little insight into the drivers of rejection pooling by banks in normal times. Using augmented data from a global survey of financial institutions, we test the relative explanatory power of country- and bank-level characteristics as drivers of trade finance rejections in emerging markets and among small and medium-sized enterprises. The analysis suggests that rejections are driven by three broad factors: those inherent to the trade finance transaction including risk and income, those which indicate a redirection of bank's business lines, such as termination of correspondent relationships, and implementation of improved client screening mechanisms. Together, these suggest that solutions to trade finance gaps are most likely to be found outside of the traditional toolbox.
Keywords: G21; F34; O19; G32; 330; Economics